3D geological modeling technology of medium-deep geothermal field in Shenshui 501 geothermal field in Damintun Sag - CONG Shufei, ZHOU Hong, ZHAO Yan, JIN Hailong, LIU Peng, WU Rongbi, CHEN Yuanchun (Youqicang pingjia yu kaifa)
As geothermal resource development continues to advance, addressing the challenge of sustainably and efficiently harnessing these resources becomes increasingly critical. This involves achieving a balance between the exploration and sustainable use（or "irrigation"） of geothermal resources. To this end, the application of Petrel, a geological modeling software originally designed for the petroleum industry, has been adapted for geothermal geological modeling, offering a promising solution. The adaptation of Petrel for geothermal purposes involves establishing a geospatial platform within the software to manage and analyze a wide range of geothermal geological data. This platform enables comprehensive research into geothermal geological elements by integrating diverse data sets to the fullest extent, thereby enhancing the quality and scope of geothermal geological studies. This approach involves scaling up from traditional small-scale oil and gas reservoir modeling to large-scale thermal reservoir modeling. Such a transition not only maintains the accuracy of the models but also aligns with the scale requirements unique to geothermal geology. Utilizing Petrel, models of the thermal reservoir temperature field, pressure field, and effective thermal reservoir can be constructed. This is achieved by combining various types of data and employing both deterministic and stochastic modeling techniques, thereby establishing a robust method for thermal reservoir geological modeling using Petrel. A key advantage of employing a 3D geological model for calculating effective thermal reservoir resources is its reduced sensitivity to reservoir heterogeneity. This approach more accurately reflects real subterranean conditions, providing a more reliable basis for resource evaluation. The resulting accurate 3D geological models and resource assessments lay a solid foundation for the numerical simulation of thermal reservoirs and the development of comprehensive thermal reservoir management plans. This, in turn, supports the scientific and sustainable exploitation and utilization of geothermal resources in the area, ensuring their efficient and responsible development.